NS1 and PA-X of H1N1/09 influenza virus act in a concerted manner to manipulate the innate immune response of porcine respiratory epithelial cells - Avanthay, Robin; Garcia-Nicolas, Obdulio; Zimmer, Gert; Summerfield, Artur (Frontiers in Cellular and Infection Microbiology, 2023)
Live-attenuated influenza A viruses (LAIV) may be superior to inactivated or subunit vaccines since they can be administered via mucosal routes to induce local immunity in the respiratory tract. In addition, LAIV are expected to trigger stronger T-cell responses that may protect against a broader range of antigen-drifted viruses. However, the development of LAIV is challenging since a proper balance between immunogenicity and safety has to be reached. In this study, we took advantage of reverse genetics to generate three LAIV based on the pandemic H1N1 2009 (pH1N1/09) virus strain: ΔPA-X, which is defective in the synthesis of the accessory PA-X protein, NS1(1-126) lacking 93 amino acids at the C-terminus of the NS1 protein, and a combination of both. Characterization of these recombinant viruses using a novel porcine bronchiolar epithelial cell line (T3) revealed that the ΔPA-X mutant replicated similar to wild type (WT) virus. However, in contrast to the parental virus the ΔPA-X mutant allowed transcription of genes involved in cell cycle progression and limits apoptosis.The NS1(1-126) mutant also replicated comparable to WT virus, but triggered the release of type I and III IFN and several chemokines and cytokines. Surprisingly, only the NS1(1-126)/ΔPA-X double mutant was significantly attenuated on T3 cells, and this was associated with enhanced transcription of genes of the innate immune system and complete absence of apoptosis induction. In conclusion, these findings indicate that NS1 and PA-X act in a concerted manner to manipulate the host cell response, which may help to develop swine LAIV vaccine with a more favorable balance of safety and immunogenicity.